Kaiser Ferdinand III. (1608-1657) Eine Biographie - Hengerer, Mark (2012)
Ferdinand III. inherited the Thirty Years' war from its father, Ferdinand II.. In the centre of his reign, the war ended in 1648 with the Peace of Westphalia and thereby the long time of the confessional arguments going along with denomination questions. The Peace of Westphalia was at the same time an important stage in the decay of the alliance of the Spanish and Austrian Habsburger which had emerged under Karl of the V. and which had polarised Europe about for one century. Now the Peace helped to create sovereign member states in Europe. For Ferdinand III. this multilayered epoch change presented itself as a number of dilemmas. These resulted from his search for peace and at the same time his attempts to fight for more favourable peace conditions; his separation from Spain against his consent and nevertheless his attempts to hold on to his Iberian relatives which were nevertheless slipping away; his timid protection of peace after 1648 and nevertheless his return against his consent to the European wars of the 1650er-Jahre. For a new comprehension of the time of Ferdinand III, it seemed important it to me to particularly stress some structural aspects, above all the close entwinement of the controversy over denominations and rule rights. In his elective monarchies, in the Empire, and in Hungary, Ferdinand III. pursued a pragmatically moderated confessional policy, in his hereditary countries, Austria and Bohemia, he was a rigid counter reformer. His counter reformation however was not only motivated religiously, but it was directed at the same time against the almost autonomous rule of the aristocracy over the rural subjects. Both confessional pragmatism and the counter reformation based on the regionally established church were a burden on the relationship Ferdinand III. to the papacy, who anyhow resisted to the dominance of the house of Habsbourg in Italy. The manuscript also provides new aspects regarding the cultural dimension of early-modern rule. The text essential stresses the pictures and terms, the symbols and rituals on which the Emperor's self understanding and his relation to the world was based and lived accordingly. Education, environment and ceremoniality take therefore much space. Rulers of the early modern times knew themselves observed and acted thereafter. If it is so difficult to determine precisely the share of Ferdinands III. of 'his' government, this is not only due to institutionalised discussions and the separation of functions within a complex government machinery. It is furthermore not only due to the fact that the Court was for the Emperor and courtiers a convincingly handled instrument of the self-manifestation with representative stage appearances on the one hand and useful concealments on the other hand. It is due above all to the fact that this Emperor did not understand governance in a modern, comprehensive sense as politics. Governance did not serve the realisation of an utopia formulated from an individual point of view or from the society. The cosmos for Ferdinand III.was still God-given, an allegedly natural order. The task of princes therein was limited, and the protection and the development of princes' rule considering the complexity of confessional and political goals and problems were in practice difficult enough. That this Emperor took up the idea of state sovereignty was a step of detachment from what he once learned to be correct. In alchemy, in magnetism and in music, Ferdinand III. continued to look for an expression of the natural order of the things. On the other hand (also here the Emperor stands at an epoch change) he was interested in a phenomenon, whose physical and artistic developments in the 17. Century destroyed the bases of his mental world: in seeing. The Emperor learned that not only the regarded object, but also the person seeing takes part in the construction of one's picture.